2001
DOI: 10.1073/pnas.041603398
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-1 binds cytoplasmic epithelial cadherin, inhibits cadherin/p120 association, and regulates stability and function of the cadherin/catenin adhesion complex

Abstract: Here we show that presenilin-1 (PS1), a protein involved in Alzheimer's disease, binds directly to epithelial cadherin (E-cadherin). This binding is mediated by the large cytoplasmic loop of PS1 and requires the membrane-proximal cytoplasmic sequence 604 -615 of mature E-cadherin. This sequence is also required for E-cadherin binding of protein p120, a known regulator of cadherin-mediated cell adhesion. Using wild-type and PS1 knockout cells, we found that increasing PS1 levels suppresses p120͞E-cadherin bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
163
2
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(180 citation statements)
references
References 41 publications
(56 reference statements)
11
163
2
4
Order By: Relevance
“…Decreased Rab7 was associated with increased g-secretase activity in early and mid MARY-X in vitro spheroidgenesis. However it had been suggested that increased g-secretase activity might dissociate E-cadherin, b-catenin, and a-catenin from the cytoskeleton, thus promoting disassembly of the E-cadherin-catenin adhesion complex, which might have negative effects on cell-cell adhesion (7,28). Thus, in the case of Mary-X well-formed spheroids, if increased g-secretase has negative effects on cell-cell adhesion, it would interfere with the formation of spheroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased Rab7 was associated with increased g-secretase activity in early and mid MARY-X in vitro spheroidgenesis. However it had been suggested that increased g-secretase activity might dissociate E-cadherin, b-catenin, and a-catenin from the cytoskeleton, thus promoting disassembly of the E-cadherin-catenin adhesion complex, which might have negative effects on cell-cell adhesion (7,28). Thus, in the case of Mary-X well-formed spheroids, if increased g-secretase has negative effects on cell-cell adhesion, it would interfere with the formation of spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…PS1, the catalytic subunit of g-secretase, reported to control g-secretase cleavage of E-cadherin (7), yields an N-terminal (PS1/NTF) and a C-terminal (PS1/ CTF) fragment. Following cleavage, the resultant PS1 fragments form a stable 1:1 heterodimer that binds to the cytoplasmic juxtamembrane region of E-cadherin (25)(26)(27)(28). For these reasons we measured PS1/NTF by Western blotting as a measurement of g-secretase activity.…”
Section: Discussionmentioning
confidence: 99%
“…The function of p120 ctn may further be modulated by presenilin through direct competition with p120 ctn for binding to cadherin (Baki et al, 2001;see Fig. 2).…”
Section: The Plot Regulatory Interactions At the Cytoplasmic Domain Omentioning
confidence: 99%
“…2). Presenilin also stimulates the interaction of E-cadherin with ␤-catenin and the cytoskeleton; the ultimate effect is to enhance adhesion (Baki et al, 2001;Georgakopoulos et al, 1999). The relationship between competition for binding of p120 ctn , enhanced binding of ␤-catenin to cadherin, and the interaction of presenilin with the cytosolic ␤-catenin complex (Murayama et al, 1998;Yu et al, 1998) remains to be clarified.…”
Section: The Plot Regulatory Interactions At the Cytoplasmic Domain Omentioning
confidence: 99%
“…Cell lines, transfections and transductions HEK293 and mouse glial C6 cells were grown in Dulbecco's modified Eagle's medium (DMEM) plus 10% fetal bovine serum (FBS) as described (Baki et al, 2001). All transfections were performed with 1 mg of cDNA using the Lipofectamine Plus TM Reagent (Invitrogen) according to manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%